THE FOUNDATIONS OF THE SCIENTIFIC METHOD AND LOGICAL APPROACH IN THE WORKS OF AL-KHWARIZMI (Eureka Journal of Humanities and Social Research, 2026)
This article provides a comprehensive analysis of the foundations of scientific methodology and logical reasoning in the works of the eminent scholar Muhammad ibn Musa al-Khwarizmi. The relevance of the study is обусловed by the growing need to reassess the historical roots of modern scientific methods, particularly within the intellectual heritage of the Eastern Renaissance. The paper examines the interrelation between empirical observation and theoretical generalization in al-Khwarizmi’s works, highlighting his systematic approach to problem-solving, logical consistency, and structured reasoning.Special attention is given to his seminal treatise Al-Kitab al-mukhtasar fi hisab al-jabr wal-muqabala, where the principles of algorithmic thinking, deductive logic, and step-by-step analytical procedures are clearly articulated. The study employs historical-philosophical analysis, comparative methodology, logical reconstruction, and system-based approaches to uncover the epistemological and methodological features of his scientific legacy.
Keywords: Al-Khwarizmi, scientific method, logical reasoning, algorithm, deduction, induction, epistemology, Eastern Renaissance, philosophy of mathematics, scientific thinking, methodological analysis, intellectual heritage.